2016
DOI: 10.1016/j.nepr.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

A teachable moment for the teachable moment? A prospective study to evaluate delivery of a workshop designed to increase knowledge and skills in relation to alcohol brief interventions (ABIs) amongst final year nursing and occupational therapy undergraduates

Abstract: The perceived value of Alcohol Brief Interventions as a tool to address alcohol misuse in Scotland has supported the establishment of a Health Improvement, Efficiency, Access and Treatment, HEAT: H4 Standard to deliver ABIs within certain health care settings. This requires that nursing, medical and allied health professionals are appropriately skilled to deliver these interventions. This study explores the knowledge and attitudes regarding alcohol misuse and related interventions among two cohorts of final ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
(14 reference statements)
1
9
0
Order By: Relevance
“…First is the importance of practice within the training. This emphasis was both clear in this study and supported by other related papers [18, 23, 29]. For Schoo and colleagues [18], the relevance of this practice was enhanced through the addition of a reflective piece and that could be considered.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…First is the importance of practice within the training. This emphasis was both clear in this study and supported by other related papers [18, 23, 29]. For Schoo and colleagues [18], the relevance of this practice was enhanced through the addition of a reflective piece and that could be considered.…”
Section: Discussionsupporting
confidence: 75%
“…Consequently, there is a dearth of research regarding student perspectives on the experience of implementation and transferability of MI skills. Prior studies examining the application of MI among clinicians have indicated the potential utility but also highlighted the implementation challenges including limited time and patient resistance [22] suggesting a need to focus on the quality of implementation not just its training [19, 23]. Further exploration of the student specific challenges facing implementation to practice is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…A number of projects have embedded SBIRT training into baccalaureate and graduate nursing education with positive outcomes, including high training satisfaction, increased knowledge, and improved attitudes, confidence, self-efficacy, and self-perceived competence toward addressing substance use. 7 - 12 An SBIRT training initiative targeting family nurse practitioner students showed that students who reported higher levels of perceived competence posttraining were more likely to screen for substance use during their clinical practice, underscoring the importance of infusing this curriculum. 8 …”
mentioning
confidence: 99%
“…Nurses and healthcare professionals have a critical role in providing motivational interviewing and behaviour change interventions in individuals (O'May et al., ; Östlund, Wadensten, Häggström, Lindqvist, & Kristofferzon, ) and organise and execute health‐promoting activities in larger groups for modifying their health risk behaviours. Based on this and other studies, healthcare professionals should consider carefully the social context and additional social constructs, such as gender, during their assessments (Koutra et al., ; Kritsotakis et al., , ).…”
Section: Relevance To Clinical Practicementioning
confidence: 99%